Wpływ kryzysu 2007–2008 na zachowania nabywców na rynku nieruchomości w Polsce - Graczyk, Beata; Łoboda, Agata (Wydawnictwo Uniwersytetu Wrocławskiego, 2011)
The aim of this article is to analyse consequences of the Global Financial Crisis of 2007 on the Residential Market in Poland. There are many indicators which determine potential buyers decisions, for example the Government’s policy or „Family on Its Own” program. The market research compare seller’s expectations and the real value of contracts on the six largest residential markets in Poland. The findings clearly show that trends on every single market are similar but changes of the price were noticed in a different quarters. The largest impact of crisis was observed on the primary market, which is not so stable as secondary market. The “Family on Its Own” Program caused increasing demand on the Residential Market in Poland. But buyers – after the Crisis- choose smaller flats, mostly with 2 or 3 rooms. The most important issue for them is price per 1m2, flat’s standard and localization. The influence for this change had also decreasing gross margin oferred by banks and fact, that more people were able to get mortgage loans. This situation could be the sign of winning throug the Global Financial Crisis in Poland but in fact it is difficult to forecast the economics trends on account of changes in the “Family on Its Own” Program and new law which will be bind mostly developers and private flat’s seller. The review all this aspects will be possible at the earliest after 2012.
Keywords: kryzys globalny; rynek mieszkaniowy; Polska